(untitled) (Ex Chordis, 2024)
In 1970, the musicologist Remo Giazotto discovered the existence of the will of the violinist Carlo Mannelli (1640-1697): this discovery had a certain resonance since, until then, very little information existed about Mannelli. The present article aims to deepen our knowledge of the Roman violinist. In particular, an analysis of the musical and historical context of his Sinfonia a violino solo e basso continuo highlights some stylistic peculiarities concerning extemporaneous ornamentation, bow dynamics and rhythm.